System Design and Development of Financial Product Sales Forecasting with exponentially weighted moving average and exponential smoothing method - Arisoma, Dianing Sandya; Supangat, Supangat; Narulita, Luvia Friska (Proceeding UII-ICABE, 2020)
There are many financial products that are offered to the customers, such as bancassurance, mutual fund or customer loan. In financial industry, the revenue of each product is calculated and summarized into one-month revenue. We can create some estimation or forecast the upcoming revenue for the upcoming month using some forecasting methods, such as moving average or exponential smoothing. In this study, we use exponential weighted moving average method and exponential smoothing. To calculate the error, Moving Average Percentage Error is used in this study. The result of this study shows that the moving average method and exponential smoothing have a pretty high error rate after calculated with Mean Average Percentage Error method. Keywords: forecasting, moving average, exponential smoothing, MAPE